Daylighting rule of thumb and typology - Nik Ibrahim, Nik Lukman; Kosman, Kamarul Afizi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2007)
Rule of thumb in daylighting has been responsible for generating typologies of building forms and elements. However, not all of these typologies perform well in daylighting. This article briefly reviews the concept of typology in architecture and proposes its application in daylighting study. Based upon the literature and recent researches in daylighting typology, the authors argue for the use of typological approach as means for analyzing and generating rule of thumb in daylighting. Simulations are conducted using Lumen Micro 8 and AGi32 softwares. The findings are suggestive that the typological approach adapted in the simulations can contribute towards development of a new rule of thumb in daylighting.